Transaneurysmal Access with Suture-Mediated Closure Device to Treat Iatrogenic Common Femoral Artery Pseudoaneurysm under Ultrasound Guidance: A Novel Technique - Shariq, Mohd; Bellam-Premnath, Krishna Prasad; Hegab, Shady (Journal of Clinical Interventional Radiology ISVIR, 2023)
We describe three cases that were complicated by access site-related common femoral artery pseudoaneurysm following therapeutic endovascular procedures. In all the cases, presentation was with painful swelling in the right groin that was tender and pulsatile on palpation; further evaluation with color Doppler ultrasound revealed pseudoaneurysm at the access site in common femoral artery. Ultrasound-guided transaneurysmal access was obtained and ProStyle (Abbott Vascular, Redwood City, California, United States) suture-mediated device was used to treat the pseudoaneurysm safely and successfully.
Keywords: pseudoaneurysm; ultrasound; closure device; transaneurysmal